Poor level of agreement on the management of postoperative pancreatic fistula: results of an international survey. Issue 4 (24th October 2012) - Melloul, Emmanuel; Raptis, Dimitri A.; Clavien, Pierre‐Alain; Lesurtel, Mickael
Abstract: Objectives: The occurrence of postoperative pancreatic fistula (POPF) is the main cause of severe complications, including death, after pancreatic surgery. This study was conduced to evaluate current practice in the management of POPF after Whipple surgery and distal pancreatectomy (DP). Methods: An online survey endorsed by the European–African Hepato‐Pancreato‐Biliary Association (E‐AHPBA) was conducted among surgical departments active in pancreatic surgery. A total of 108 centres were contacted by e‐mail. The survey focused on the use and timing of drainage, nutrition strategies, provision of somatostatin and antibiotic therapies, imaging strategy and indications for reoperation when POPF is diagnosed after pancreatic surgery. Results: A total of 55 centres (51%) completed the survey. Overall, responses showed poor agreement among centres (Fleiss' kappa: <0.40) on 89% of items after Whipple surgery and 78% of items after DP. There was very poor or no agreement (Fleiss' kappa: <0.1) on postoperative strategies for the management of nutrition and use of somatostatin after both procedures. In the event of POPF, 42% of centres used total oral nutrition and 22% used somatostatin after Whipple surgery, and 71% used total oral nutrition and 31% used somatostatin after DP. There were significant disagreements between units conducting, respectively, more and fewer than 50 Whipple procedures per year on drain removal after DP, and imaging strategy and patient discharge after Whipple surgery and DP. Conclusions: This survey discloses important disagreements worldwide regarding the management of POPF after both Whipple surgery and DP. The standardized management of POPF would better facilitate the comparison of outcomes in future trials.